2000
DOI: 10.2307/2667075
|View full text |Cite
|
Sign up to set email alerts
|

How Experience and Network Ties Affect the Influence of Demographic Minorities on Corporate Boards

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.This content downloaded from 128.83.205.78 on Thu,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
468
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 617 publications
(491 citation statements)
references
References 111 publications
15
468
0
8
Order By: Relevance
“…Burke (2000) argues that board selectors held the assumption that women lack adequate human capital for board positions. This argument is empirically supported by Westphal and Milton (2000) and Singh et al (2008), who reported that women directors are less likely to have top manager or focal director experience than men directors. In the same vein, 15 Catalyst (1993) showed that CEOs were reluctant to appoint women as directors of BDs because they believe that females are unqualified.…”
supporting
confidence: 59%
“…Burke (2000) argues that board selectors held the assumption that women lack adequate human capital for board positions. This argument is empirically supported by Westphal and Milton (2000) and Singh et al (2008), who reported that women directors are less likely to have top manager or focal director experience than men directors. In the same vein, 15 Catalyst (1993) showed that CEOs were reluctant to appoint women as directors of BDs because they believe that females are unqualified.…”
supporting
confidence: 59%
“…A survey conducted in America by Ernst & Young found that many firms in Europe and America complain that they struggle to find experts to be board members. Thus, many boards in the US have appointed directors with experience from other firms and industries (Westphal & Milton 2000).…”
Section: Non-executive Director Rolesmentioning
confidence: 99%
“…Ajoutons à ceci qu'en étant indépendants, les administrateurs accomplissent efficacement leurs fonctions (le code de 'best practices', 1999) et prennent les bonnes décisions dans certaines situations telles que le remplacement d'un dirigeant non performant (Weisbach, 1988), le recrutement externe du dirigeant dans le cas où la performance de la firme diminuerait considérablement (Huson, Parrino et Starks, 2001), les acquisitions et la résistance aux offres d'achat (Byrd et Hickman, 1992). Par ailleurs, les administrateurs externes en siégeant dans des conseils d'administration d'autres entreprises 1 , ils acquièrent des compétences et de l'expé-rience (Kosnik, 1987) ce qui leur permet de contribuer efficacement à la prise de décisions (Westphal et Milton, 2000) et d'assurer un niveau élevé de transparence (Gul et Leung, 2004). De plus, la gouvernance s'améliore si l'élection des administrateurs est annuelle (Jensen, 1993;Webb, 2004), si ces derniers occupent des postes de dirigeants dans d'autres entreprises (Shivdasani, 1993) et si la présence de femmes administrateurs se fait plus fréquente (Carter, Simkins et Simpson, 2003) ou si encore les administrateurs âgés de moins de 69 ans sont plus nombreux (Core, Holthausen et Larcker, 1999).…”
Section: La Bonne Gouvernance : Un Nouveau Conceptunclassified